Geographic distributions in Chromosera species—continental and oceanic barriers, including a new species, a new variety and a new combination - Grootmyers, Django; Mullineux, Sahra-Taylor; Redhead, Scott A.; Bau, Tolgor; Horman, Joel; Kerner, Ron; Lebeuf, Renée; Sergeev, Alexey; Tomko, Paul; Wasilewski, David; Ré, Lauren A.; Hickey, Sadie; et al. (Phytotaxa, 2025)
Chromosera cyanophylla was initially described from Europe and, when it was named type of the genus, was thought to be distributed throughout Europe and North America. Molecular phylogenies revealed that Chromosera “cyanophylla” from eastern and western North America represent two separate species and that neither is conspecific with European C. cyanophylla nor with the more recently described C. ambigua. Here we describe a new species from western North America as Chromosera loreleiae. We resurrect the species Peck described from eastern North America as Agaricus lilacifolius by recombining it in Chromosera and describe a new lilac variety lacking yellow pigments. The range of C. cyanophylla s.s. across eastern Eurasia including China is confirmed. Chromosera citrinopallida, described from Washington state, USA, comprised one clade in Washington that we infer is C. citrinopallida s.s. and a separate circumarctic clade distributed in Scandinavia, Iceland and Alaska.